Islam, New Media and Young Muslims Radicalization - Piwko, Aldona (Journal for the study of religions and ideologies, 2025)
The aim of the article is to present the phenomenon of radicalization of young Muslims from both Muslim countries and Western Europe, which takes place using new media. The paper uses the method of critical analysis of sources because it allows the interpretation of facts and relating them to the motives of conduct and the increase in popularity of radical religious movements. Referring to the theory of mediation and mediatization of religion, the article analyzes the impact of new media on Islam and presents some of their effects, which contribute to the creation of a radical version of this religion. The radicalization of religious views among young Muslims takes place on three levels: religious-cultural, social and political. All of these fields are dominated by social media. Ease of access to them gives a sense of belonging to the global Islamic community, which results in the belief in the unique strength and unlimited possibilities of the entire community. In their analysis, the authors showed the relationship between the characteristics of new media users and their low resistance to the propaganda of radical Islamist movements and terrorist groups used against them, as well as the opportunities that new media provide to terrorist groups in using Islam to build and strengthen their structures.